2022
DOI: 10.3389/fpsyt.2022.796719
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Therapy of Psychosis Spectrum Disorders in a Real-World Setting: Antipsychotics Prescription Patterns and Long-Term Benzodiazepine Use

Abstract: BackgroundMaintenance therapy of patients with primary psychosis spectrum disorders (PSD) in the Western Balkans has received limited interest so far. The present study aimed to investigate long-term prescription patterns among outpatients with PSD.MethodsInformation about prescription of antipsychotics (AP), benzodiazepines (BZD) and other psychotropic medication over a 6-month period was collected from outpatients (n = 134; ICD-10 diagnosis F20-29) recruited by a larger multi-site study, to find mean daily n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Some studies have suggested that use is more widespread in Western countries [ 23 ], but there may be a lack of data from CEE countries, as some authors have pointed out [ 14 ]. However, these results are consistent with studies from Eastern Europe indicating a high number of patients treated with benzodiazepines for long periods of time [ 24 ]. Interestingly, antipsychotics were more likely to be recommended among participants in CEE compared to NE countries.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have suggested that use is more widespread in Western countries [ 23 ], but there may be a lack of data from CEE countries, as some authors have pointed out [ 14 ]. However, these results are consistent with studies from Eastern Europe indicating a high number of patients treated with benzodiazepines for long periods of time [ 24 ]. Interestingly, antipsychotics were more likely to be recommended among participants in CEE compared to NE countries.…”
Section: Discussionsupporting
confidence: 91%